Blade Runner 2049 the storyboards - Hudecki, Sam; Henley, Darryl; Villeneuve, Denis 1967- (Titan Books, 2021)
"Blade Runner 2049: The Storyboards is a celebration of the rarely-seen artwork that was key in building the harsh, yet strangely beautiful, environments in the film. This remarkable book presents a fresh look at Blade Runner 2049, including scenes that were later altered or cut out entirely, along with new, in-context commentary from storyboard artists Sam Hudecki and Darryl Henley throughout."--Amazon.com
Keywords: Blade runner 2049; Storyboard; Blade runner 2049 (Motion picture); Bildband